2011
DOI: 10.1094/cm-2011-0127-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Soybean, Canola, and Mustard Meals as Organic Sources of Nitrogen for Potatoes in Northern New England

Abstract: Canola (Brassica napus), soybean (Glycine max), and mustard (Brassica juncea) oilseed meals were compared to three forms of synthetic N (ammonium nitrate, urea, and ammonium sulfate) in order to evaluate their relative value as sources of N for organic potato (Solanum tuberosum) production. Two trials were conducted in Maine where each oilseed meal was broadcast applied to deliver 150 lb total N per acre and tilled in ahead of planting and compared with the synthetic forms of N applied in the same manner (150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The percentages of N mineralized from Phytaboost and Sustane were similar to values previously reported for soybean meal and poultry litter. Sexton and Jemison (2011) reported that 75% of the N in soybean meal was mineralized into an organic potato field within 3 mo of application. These grits also mineralized similar amounts of N as high‐organic‐N fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…The percentages of N mineralized from Phytaboost and Sustane were similar to values previously reported for soybean meal and poultry litter. Sexton and Jemison (2011) reported that 75% of the N in soybean meal was mineralized into an organic potato field within 3 mo of application. These grits also mineralized similar amounts of N as high‐organic‐N fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…Fertilization consisted of soybean meal (7-1-1 N-P-K, non-GMO soybean meal; Zeeland Farm Services Inc., Zeeland, MI) broadcast at 1400 kg/ha before preplant striptillage or cultivation each year for all treatments. This rate was intended to meet crop phosphorus (P) and potassium (K) demands based on the soil test nutrient analysis, and to provide most crop N requirements after potential legume cover crop N inputs based on the assumption that $75% of the 98 kg N/ha applied in the soybean meal would be available during the year of application (Carlson et al 2020;Sexton and Jemison 2011;Sullivan et al 2019). During all years, insect arthropod pests were monitored, and their densities were found to be below the typical thresholds that would have justified pesticide application.…”
Section: Methodsmentioning
confidence: 99%
“…Crop fertility and weed management, within the confines of the certified organic regulations [5], are major concerns in organic production systems, as methods other than synthetic chemicals must be utilized. Alternative organic-approved nutrient sources include manures [6][7][8][9] and seed meals [9][10][11], when derived from certified organic materials.…”
Section: Introductionmentioning
confidence: 99%